The Effect of Small Size Uterine Fibroids on Pregnancy Outcomes in High-risk Pregnancies - Cagan,Murat (2020)
Abstract Objective To evaluate the obstetric outcomes of singleton high-risk pregnancies with a small size uterine fibroid. Methods This retrospective cohort study was conducted among 172 high-risk pregnant women who were followed-up by a single surgeon between 2016 and 2019. Pregnant women with preconceptionally diagnosed small size (< 5 cm) single uterine fibroids (n = 25) were compared with pregnant women without uterine fibroids (n = 147) in terms of obstetric outcomes. Results There was no statistically significant difference between the groups in terms of adverse pregnancy outcomes. The size of the fibroids was increased in 60% of the cases, and the growth percentage of the fibroids was 25% during pregnancy. Intrapartum and short-term complication was not observed in women who underwent cesarean myomectomy. Conclusion Small size uterine fibroids seem to have no adverse effect on pregnancy outcomes even in high-risk pregnancies, and cesarean myomectomy may be safelyperformed in properly selected cases.